Missing out on the “Men’s Club”: Gendered Attitudes to Intrapreneurship within Large Corporations - Philip Meier; Simon Adderley (Research Synergy Foundation, 2021)
This paper explores the factors that influence innovative and intrapreneurial behaviour amongst female employees. The paper explores a case study of one business unit (of approximately 1,100 employees) within a much larger corporation. It uses a qualitative methodology of semi-structured interviews to explore (1) the factors that influence innovative and intrapreneurial behaviour amongst female employees and (2) how these factors are influenced by the organisation. The paper is part of an emerging research agenda that explores gendered attitudes to intrapreneurial behaviour. This is an extremely under-researched area of research which tends to borrow heavily from studies into female self-employment. The paper demonstrates that rather than focus upon female attitudes to risk or lifestyle choices, the primary issue facing potential female intrapreneurs is implicit and explicit gatekeeping by male-dominated